Structural, magnetic and fluorescence characterization of europium(III) azomethine complexes with asymmetric ligands. (1st May 2021) - Khayarov, Khasan; Pyataev, Andrew; Saifutdinov, Alexander; Galiakhmetova, Diana; Emelianov, Dmitrii; Rakhmetova, Elvira; Gubaidullin, Aidar; Galkina, Irina; Galkin, Vladimir
Graphical abstract: Abstract: In this work, complexes of europium (III) based on β-naphthol and phenol were synthesized and investigated by the methods of Mössbauer spectroscopy, NMR spectroscopy, thermogravimetry, mass spectroscopy. It was found that the structure of the studied complexes determines the spin state of the central ion. The β-naphthol-based complex exhibits diamagnetic properties (S = 0), and the complex, where the ligand is phenol-based azomethine, is paramagnetic (S = 3). It was shown that the studied complexes exhibit a broad spectral response upon excitation in the ultraviolet part of the spectrum.